The Effect Of Sales Promotion And Social Media Marketing On The Purchase Intention Of BSI Gold Products Through Perceived Value, Brand Awareness, Trust, And Customer Engagement As Mediation Variables: Systematic Literature Review (SLR) With Bibliometrics - Nasihiyah Purwaning Wulan; Budi Eko Soetjipto; Madziatul Churiyah (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the influence of Sales Promotion and Social Media Marketing on the Purchase Intention of BSI Gold products by considering the mediating role of Perceived Value, Brand Awareness, Trust, and Customer Engagement in the Madiun Raya area. The method used is Systematic Literature Review (SLR) with a bibliometric approach to identify, categorize, and analyze the latest research trends related to factors influencing consumer purchasing decisions in the Islamic banking sector. The results of the analysis show that Sales Promotion and Social Media Marketing have a positive influence on Purchase Intention, either directly or indirectly through mediation variables. These findings underscore the importance of promotional strategies that are integrated with strengthening perceived value, building brand awareness, increasing trust, and managing customer interactions to drive consumer purchase decisions. This study provides theoretical and practical contributions to the development of marketing strategies for Islamic banking products, while offering further research directions using bibliometric methods to explore the relationship between digital marketing variables.